2015
DOI: 10.1177/1756287215577329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of triptorelin pamoate 11.25 mg administered subcutaneously for achieving medical castration levels of testosterone in patients with locally advanced or metastatic prostate cancer

Abstract: This study demonstrates that triptorelin pamoate 11.25 mg administered by the subcutaneous route every 3 months is as efficacious and well tolerated as administration via the intramuscular route in men with locally advanced or metastatic prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Patients are also offered greater flexibility by the availability of subcutaneous (SC) injections of triptorelin [ 31 ]. The IM route of administration may not be suitable for all patients (for example, the risk of excessive bleeding or haematomas in those receiving anticoagulants) [ 32 ], and so SC injections provide an alternative delivery option.…”
Section: Triptorelin As Adtmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients are also offered greater flexibility by the availability of subcutaneous (SC) injections of triptorelin [ 31 ]. The IM route of administration may not be suitable for all patients (for example, the risk of excessive bleeding or haematomas in those receiving anticoagulants) [ 32 ], and so SC injections provide an alternative delivery option.…”
Section: Triptorelin As Adtmentioning
confidence: 99%
“…The IM route of administration may not be suitable for all patients (for example, the risk of excessive bleeding or haematomas in those receiving anticoagulants) [ 32 ], and so SC injections provide an alternative delivery option. The key pharmacokinetic parameters (such as C max and C min ) with the SC injection of a triptorelin pamoate 11.25 mg 3-month formulation are in the same range as observed for the IM injection [ 30 , 31 ].…”
Section: Triptorelin As Adtmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rising PSA levels are commonly used to diagnose CRPC in the clinic, with a minority of oncologists or urologists citing testosterone levels as an additional marker, according to a European survey 5. Clinical trials have continued to use the <1.7 nmol/L testosterone cutoff, although some studies are starting to explore lower cutoff values 12. A recent trial found that gonadotropin-releasing hormone agonist therapy was associated with a 90.0% probability of maintaining serum testosterone levels of <0.7 nmol/L up to 26 weeks, compared with a 96.0% probability of testosterone levels of <1.7 nmol/L (95% CI, 85.0–95.0 and 92.0–99.0, respectively) 12…”
Section: Defining Medical Castration With Adtmentioning
confidence: 99%
“…Likewise, the route of administration (i.m. or s.c.) appears to have minimal impact upon the pharmacological suppression of testosterone [19]. The pharmacokinetic properties of these formulations are summarised in Table 1 [12,[20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%